Special features of adaptation model of intellectual rights defence on the modern stage of state formation - Троцюк, Ніна Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article deals with forms and methods of the copyright protection. The present state of the legal protection of the copyright is investigated and legislative reforms in the field of the property of intellectual rights are analyzed. The adaptive model of copyright protection is proposed on the basis of the conducted research. With development of information technology and availability of Internet access, objects of copyright law are more widely used, which leads to significant violations of intellectual property rights . Often such violations occur due to insufficient knowledge of Ukrainian legislation, insufficient usage of protective hardware hardware, usage of various technical devices and technological developments to circumvent copyright protection, improper legal processing of operations related to the transfer of intellectual property rights. It should be noted that over the past few years Ukraine has taken significant steps towards improving legal protection of copyrights. The Law of Ukraine "On State Support to Cinematography in Ukraine" was adopted; the draft Law of Ukraine "On Amendments to Certain Legislative Acts of Ukraine on the Protection of Copyright and Related Rights in the Internet" is at the stage of final adoption; the draft Law of Ukraine "On Collective Management of Property Rights Subjects of Copyright and Related Rights the State Service of Intellectual Property was reformed and the functions on implementation of the state policy in the field of intellectual property were transferred to the Ministry of Economic Development and Trade of Ukraine, the norms of the current legislation are adapted to the international legal norms. The purpose of this article is, based on the diagnostic approach, to develop an adaptive model of copyright protection, which contains the interconnection of remedies and relevant institutions, and unlike the existing ones, characterizes the effectiveness of methodological and institutional protection of copyright, which allows achieving compliance with the requirements of protection of intellectual property in countries of the European Union. The articles and forms of copyright protection investigated in the article, the corresponding institutions providing protection of intellectual property rights, legislation, mechanisms of interaction between them gave an opportunity to develop an adaptive model of copyright protection. This adaptive protection model is based on the principles of rationalism and logic and is a multi-purpose model, since the results of its implementation achieve two goals: reducing the number of copyright infringement cases and reducing the cost of resources to ensure copyright protection. The adaptive defense model constructed accurately describes the relationship between the effectiveness of the system and the process of ensuring copyright protection.